Harry Potter and the half-blood prince - Heyman, David, 1961-; Barron, David; Kloves, Steven; Yates, David, 1963-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Broadbent, Jim.; Bonham Carter, Helena, 1966-; Coltrane, Robbie; Davis, Warwick; Gambon, Michael; et al. (Burbank, Calif. : Warner Home Video, 2009)
Emboldened by the return of Lord Voldemort, the Death Eaters are wreaking havoc in both the Muggle and wizarding worlds. Hogwarts, once thought to be a safe haven, may no longer be safe.
Title from container.
Based on the novel by J.K. Rowling.
Director of photography, Bruno DelBonnel ; editor, Mark Day ; score composer, Nicholas Hooper.
Daniel Radcliffe, Rupert Grint, Emma Watson, Jim Broadbent, Helena Bonham Carter, Robbie Coltrane, Warwick Davis, Michael Gambon, Alan Rickman, Maggie Smith, Timothy Spall, David Thewlis, Julie Walters.
Rating: PG; for scary images, some violence, language and mild sensuality.
DVD.
Keywords: Potter, Harry (Fictitious character) -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Drama; Wizards -- England -- Drama; Teenagers -- Conduct of life -- Drama; Good and evil -- Drama; Fantasy films; Action and adventure films; Feature films; Films for the hearing impaired